2020
DOI: 10.3389/fimmu.2020.00586
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Ferritin Levels Before Start of Conditioning With Mortality After alloSCT – A Prospective, Non-interventional Study of the EBMT Transplant Complications Working Party

Abstract: Frontiers in Immunology | www.frontiersin.org April 2020 | Volume 11 | Article 586 Penack et al. Ferritin and alloSCT Outcomehigher infection-related mortality in the high ferritin group (HR = 3.9, CI = 1.6-9.7, p = 0.003). Acute and chronic GVHD incidence or severity were not associated to serum ferritin levels. We conclude that ferritin levels can serve as routine laboratory biomarker for mortality risk assessment before alloSCT.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
(38 reference statements)
2
5
1
Order By: Relevance
“…Although patients with hematological malignancies usually receive multiple high‐dose chemotherapies before transplant and have accumulated organ toxicity, 22 these patients may have a poorer functional reserve of organs and are therefore susceptible to organ failure, which is one of the main contributors to increased nonrelapse mortality 23 . Our data again confirmed that elevated pretransplant SF increased the risk of bloodstream infection and fungal infection, 24,25 but no trend toward more infection‐related death was observed. We assumed intensive treatment for infection may reduce infectious deaths, thereby underestimating the impact of SF on TRM and OS.…”
Section: Discussionsupporting
confidence: 71%
“…Although patients with hematological malignancies usually receive multiple high‐dose chemotherapies before transplant and have accumulated organ toxicity, 22 these patients may have a poorer functional reserve of organs and are therefore susceptible to organ failure, which is one of the main contributors to increased nonrelapse mortality 23 . Our data again confirmed that elevated pretransplant SF increased the risk of bloodstream infection and fungal infection, 24,25 but no trend toward more infection‐related death was observed. We assumed intensive treatment for infection may reduce infectious deaths, thereby underestimating the impact of SF on TRM and OS.…”
Section: Discussionsupporting
confidence: 71%
“…( 116 ), SF > 2000 ng/mL before HSCT was identified as an independent risk factor for primary PGF and a strong poor prognostic factor. In a subsequent prospective multicenter study, patients with SF > 1500 ng/mL before the start of conditioning with allo-HSCT had an inferior OS (hazard ratio, 2.5, CI = 1.5-4.1, P = 0.0005) and progression-free survival (hazard ratio, 2.4, CI = 1.6-3.8, P < 0.0001) ( 117 ). In contrast, in a prospective cohort study using liver magnetic resonance imaging to quantify the liver iron content, there was no significant correlation between IO (liver iron content >1.8 mg/g) before allo-HSCT and the cumulative incidence of multiple complications, OS, or NRM after HSCT ( 118 ).…”
Section: The Soilmentioning
confidence: 99%
“…In contrast, in a prospective cohort study using liver magnetic resonance imaging to quantify the liver iron content, there was no significant correlation between IO (liver iron content >1.8 mg/g) before allo-HSCT and the cumulative incidence of multiple complications, OS, or NRM after HSCT ( 118 ). Interestingly, using SF or the liver iron content as a marker of IO revealed that IO was not related to the occurrence of acute or chronic GVHD ( 117 , 118 ). Hepcidin expressed by the liver, it modulates iron absorption and release and is overexpressed when IO decreases these processes, and the erythropoiesis demands can eventually not be met ( 119 ).…”
Section: The Soilmentioning
confidence: 99%
“…Moreover, considering that allo-HSCT patients frequently exhibit high serum ferritin levels and that iron overload affects their prognosis, ELT iron chelation properties could be helpful in the recovery of BM microenvironment fitness, ameliorating their clinical course ( Penack et al, 2020 ). Considering the ELT-related risk of clonal evolution and leukemic cells proliferation, studies are needed to investigate whether the ELT range of beneficial effects in PGF could extend to treating acute GvHD without affecting GvL.…”
Section: Pgf: Keeping the Balancementioning
confidence: 99%